Comparative Evaluation of pH and In Vitro Cytotoxicity of Zinc Oxide–Ozonated Eugenol and Conventional Zinc Oxide Eugenol as Endodontic Sealers - Ravivarman, Chandramohan (J Pharm Bioallied Sci, 2020)
BACKGROUND: Eugenol released from zinc oxide eugenol (ZOE)–based sealants may cause irritation to the periapical tissues and has cytotoxic potential. Ozone therapy has numerous clinical applications with humans because of its bactericidal action, detoxifying effect, stimulation of angiogenesis, and wound-healing capacity. Therefore ozone can be incorporated in ZOE sealer to exploit these properties. MATERIALS AND METHODS: Eugenol was ozonated using ozonator machine and the samples were divided into two groups: Group I: zinc oxide eugenol (n = 10) and Group II: zinc oxide–ozonated eugenol (OZOE; n = 10). The pH of the fresh sealer samples and the set samples was measured using calibrated pH meter after predetermined time intervals. Cytotoxicity of the set sealer was evaluated on mouse L929 fibroblasts using cellular metabolic assay. RESULTS: pH of the samples in Group II was higher when compared to Group I. Group II showed higher cell viability than the Group I. CONCLUSION: OZOE sealers can be used as an alternative to the conventional ZOE sealers.